Information literacy in Colombia: report of the state of the art (2011)
ABSTRACT: This report has been developed following a number of strategies (methods and technical/research instruments), namely documentary research, web content analysis, qualitative fieldwork and online surveys. This research was conducted in two contexts: in university libraries, public library networks and compensation funds libraries (mixed) and in research groups within the areas of information science, education and psychology in different cities. It focuses on the current state of information literacy in Colombia from the perspective of implementing educational programmes and projects at different types of libraries, educational levels as well as from the teaching and research perspectives. KEYWORDS: Information literacy training, information skills, university libraries, school libraries, public libraries, research groups, librarian education, Colombia